Dose and Frequency of PGF2α Administration to Lactating Dairy Cows Exposed to Presynchronization and Either Five- or Seven-day Ovsynch Protocols: Ovulation, Luteolysis, and Pregnancy Rates - J. S. Stevenson; J. A. Sauls (Kansas Agricultural Experiment Station Research Reports, 2017)
Lactating Holstein cows in one herd were milked three times daily and enrolled in a 2 × 2 × 2 factorial design with eight treatments before first postpartum artificial insemination (AI). These treatments were employed to test ovulatory, progesterone, and luteolytic outcomes to three main effects: (1) two GnRH-PGF2αpresynchronization programs (PG-3-G vs. Double Ovsynch); (2) 5- vs. 7-day Ovsynch-duration programs; and (3) two doses (25 mg on consecutive days) or one dose (50 mg) of PGF2αadministered before timed AI. Results from this experiment demonstrate no differences in the presynchronization treatments of PG-3-G vs. Double Ovsynch; both are effective in initiating estrous cycles during warm-hot vs. cool-cold seasons. Although ovulatory responses were similar after the first GnRH administration, Double Ovsynch cows tended to have greater ovulation responses after the second GnRH administration. The single large, one-time administered 50-mg dose was effective in causing luteolysis in the 7-day program but slightly less effective in the 5-day program. Thus, when using the shorter 5-day program, the two 25-mg PGF2αdoses administered 24 hours apart are recommended. Insufficient numbers of cows were treated to make conclusions about pregnancy outcomes in this one-herd study. Pregnancy rates, however, were reduced in 5-day Ovsynch program when the single large 50-mg dose of PGF2αwas employed.
Keywords: Gonadotropin-releasing hormone; presynchronization; luteolysis; Ovsynch; PGF2α; pregnancy rates